Supplemental Material: Oligocene-Neogene lithospheric-scale reactivation of Mesozoic terrane accretionary structures in the Alaska Range suture zone, southern Alaska, USA - T.S. Waldien (9012115); (281964) (2020)
U-Pb and 40Ar/39Ar data for samples presented herein.